international Teaching Practicum - Azizah, Nur (Sebelas Maret University, 2016)
his paper explores the experience of four pre-service special education teachers from Universitas Pendidikan Sultan Idris (UPSI) Malaysia who undertook two months teaching practice in a Special Schoolin Yogyakarta. Using qualitative data from an open-ended questionnaire, the pre-service special educationteachersâ experienced is investigated. The findings show that the experience is positive.